(untitled) (Dhaka University Journal of Pharmaceutical Sciences, 2023)
The study attempted to illustrate the antioxidant, thrombolytic and cytotoxic properties of two different medicinal plants, Jatropha pandurifolia and Syzygium reticulatum. In vitro antioxidative activity was tested through qualitative and quantitative DPPH scavenging assay which revealed the radical scavenging activity. Methanolic stem bark extract of Jatropha pandurifolia (MSJP) and ethyl acetate leaf extract of Syzygium reticulatum (EALSR) showed moderate clot rupture activity, the value of which were 61.30 ± 2.35% (**P<0.01) and 63.81 ± 1.92% (**P<0.01) accordingly, whereas streptokinase showed 73.6 ± 0.76% clot lysis capability. IC50 value was 6.82 ± 0.99 μg/mL for butylated hydroxy toluene (BHT) wherein MSJP and EALSR showed 8.1± 1.44 (***P<0.001); and 10.34±2.12 (**P<0.01) μg/mL accordingly. In Brine shrimp cytotoxicity, MSJP, EALSR and vincristine sulphate exhibited mild activity with LC50, the value of which were 5.73±2.85 (*P<0.05), 5.12±1.57 (*P<0.05) and 0.52 ± 0.18 μg/mL respectively. The results proved the presence of many bioactive compounds showing thrombolytic, antioxidative and cytotoxic activities. Dhaka Univ. J. Pharm. Sci. 22(1): 97-103, 2023 (June)